Partnership for improved access to agro-inputs and technology: Some experiences from the emergency rice initiative project in Ghana - Dogbe, W.; Sogbedji, J.; Mando, A.; Buah, Saaka S.J.; Nutsugah, S.K., Kanton, R.A.L.; Atokple, I.D.K.; Amankwah, A.; Wiredu, A.N.; Karikari, A.S.; Djamon, K.; Osei, C.; Ajayi, O.; et al. (Academic Journals, 2012)
A two-year emergency rice (Oryza sativa L.) initiative project was launched in 2009 in response to the global rice crisis in 2008. The objective of this initiative in Ghana was to increase rice productivity in order to improve food security. Project activities included seed fairs, dissemination of information on improved production technologies using videos and rural radios, training of agro-input dealers,extension officers and farmers as well as promotion of best-bet practices through field demonstrations.The project made progress in strengthening the ability of agro-input dealers to create business linkages with input suppliers and extend their retail networks to rice farmers. Overall, 34 agro-input dealers were trained, in collaboration with the Ghana Agro-dealer Development project, on agro-input business management, product knowledge and rice production. Thirteen agro-input dealers were assisted to access credit for business development. Better financed, trained agro-dealers were then able to provide over 12,600 rice farmers with improved seed, mineral fertilizers, technical advice on agro-input use and the promotion of improved agronomic practices through field demonstrations. Some agro-input dealers even provided free inputs for the conduct of demonstrations on new products and good agronomic practices. On average, fertilizer application in demonstration trials increased paddy yields by 68 to 80%over the farmer practice of no fertilizer application. For the participating farmers, there were significant increases in rice paddy yields, reductions in the cost of operations and improvements in the contribution of rice to household incomes. The results suggest that a holistic and multi-stakeholder partnership is an efficient way to improve the access by small-holder resource-poor farmers to agro-inputs and technology and also an effective way to grow the rural agro-input market